2011
DOI: 10.11564/25-2-231
|View full text |Cite
|
Sign up to set email alerts
|

Magnitudes and trends in orphanhood amongyounger persons in the era of HIV/AIDS inSouth Africa, 2001-2015

Abstract: Information on the magnitude of orphanhood is important from various perspectives. Though not designed for that purpose, orphanhood questions have been used by some studies to infer the magnitude of orphans due to AIDS among younger persons. This study provides an historical overview of the orphanhood questions and estimates the magnitude of orphans in the era of HIV/AIDS in South Africa using an epidemiologic and demographic model. The results suggest that the number of orphans in South Africa may increase to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…An ‘adoption effect’ in which interviewers or respondents report information about non-biological rather than biological parents has been described elsewhere [ 65 ]. In South Africa, Udjo (2011) has also suggested that African households are more likely to over-report paternal deaths than other population groups [ 67 ]. In this study however, the effects of response bias on orphanhood estimates are likely to be small given the numerous visits to households to update ACDIS information and, specific attention in questionnaire design and interviewer training.…”
Section: Discussionmentioning
confidence: 99%
“…An ‘adoption effect’ in which interviewers or respondents report information about non-biological rather than biological parents has been described elsewhere [ 65 ]. In South Africa, Udjo (2011) has also suggested that African households are more likely to over-report paternal deaths than other population groups [ 67 ]. In this study however, the effects of response bias on orphanhood estimates are likely to be small given the numerous visits to households to update ACDIS information and, specific attention in questionnaire design and interviewer training.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigates the relationship between multiple care responsibilities and stress proliferation contributing to depression among Black and Colored 1 HIV grandparent caregivers in the Western Cape area of South Africa. Estimates of the number of AIDS orphans in South Africa range from 1.9 million (Udjo, 2011) to 3.7 million (United Nations Children’s Fund [UNICEF] South Africa, 2014).…”
Section: Introductionmentioning
confidence: 99%